2004
DOI: 10.1074/jbc.m401552200
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Peroxisome Proliferator-activated Receptor Agonists with a Novel Binding Epitope Shows Antidiabetic Effects

Abstract: The peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors belonging to the NR1 subfamily of nuclear receptors. The PPARs play key roles in the control of glucose and lipid homeostasis, and the synthetic isoform-specific PPAR agonists are used clinically to improve insulin sensitivity and to lower serum triglyceride levels. All of the previously reported PPAR agonists form the same characteristic interactions with the receptor, which have been postulated to be important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 40 publications
9
46
0
2
Order By: Relevance
“…The overall fold was almost identical to previously determined apo and complex structures, [28][29][30] and comprised of 12 helices (H1-H12) and a small b-sheet region of four strands (Figure 1a). We superposed Ca atoms from the structure of PPARg with telmisartan onto those from the structure with rosiglitazone (PDB ID: 2PRG), 29 2-BABA (PDB ID: 1WM0) 30 and the apo structure (PDB ID: 1PRG), 29 and calculated root mean square deviations. The root mean square deviations were 0.64 Å for rosiglitazone, 0.69 Å for 2-BABA and 0.93 Å for the apo structure.…”
Section: Structure Of the Pparc Complexed With Telmisartansupporting
confidence: 80%
See 2 more Smart Citations
“…The overall fold was almost identical to previously determined apo and complex structures, [28][29][30] and comprised of 12 helices (H1-H12) and a small b-sheet region of four strands (Figure 1a). We superposed Ca atoms from the structure of PPARg with telmisartan onto those from the structure with rosiglitazone (PDB ID: 2PRG), 29 2-BABA (PDB ID: 1WM0) 30 and the apo structure (PDB ID: 1PRG), 29 and calculated root mean square deviations. The root mean square deviations were 0.64 Å for rosiglitazone, 0.69 Å for 2-BABA and 0.93 Å for the apo structure.…”
Section: Structure Of the Pparc Complexed With Telmisartansupporting
confidence: 80%
“…Although we obtained plate-like crystals that belonged to space group C2 from the solution containing PPARg and telmisartan and found lattices similar to those found when PPARg LBD formed complexes with other agonists, [28][29][30] we did not observe telmisartan in the determined structure.…”
Section: Structure Of the Pparc Complexed With Telmisartanmentioning
confidence: 58%
See 1 more Smart Citation
“…It is well known that most PPAR␥ ligands are able to normalize glycemia and insulinemia in spite of increasing body weight (22,24). This has first been observed with TZDs in animal studies (31,32,51) and then confirmed in mildly obese humans treated with such compounds (33,34).…”
Section: Discussionmentioning
confidence: 81%
“…1F). However, the finding that it has no effect on adipogenesis-in addition to the significant effect in reducing atherosclerosis-showed functional differences with rosiglitazone and other PPAR␥ agonists (21)(22)(23)(24)(25)(26)(27). This establishes S 26948 as a new specific PPAR␥ modulator that is able to drive normal adipocyte differentiation-in contrast to rosiglitazone, which exacerbates this process.…”
Section: Discussionmentioning
confidence: 99%